Universal spin-dependent variable range hopping in wide-band-gap oxide ferromagnetic semiconductors - 代由勇 颜世申 田玉峰 陈延学 刘国磊 梅良模 (Chinese physics B, 2010)
This paper proposes a universal spin-dependent variable range hopping theoretical model to describe various experimental transport phenomena observed in wide-band-gap oxide ferromagnetic semiconductors with high transition metal concentration. The contributions of the ＇hard gap＇ energy, Coulomb interaction, correlation energy, and exchange interaction to the electrical transport are considered in the universal variable range hopping theoretical model. By fitting the temperature and magnetic field dependence of the experimental sheet resistance to the theoretical model, the spin polarization ratio of electrical carriers near the Fermi level and interactions between electrical carriers can be obtained.